Is ’n kerkorde nie kragtens sy aard strydig met die werking van die Heilige Gees nie? - C. J. Smit (In die Skriflig, 2008)
Is a church order, according to it’s nature, not contrary to the work of the Holy Spirit? The question is whether a church order should be seen as anti- Spiritual. Does a church order, in contrary to the work of the Holy Spirit, lead to rigidity of the church? By this question the controversy of the spiritual life of the church versus the institutional ordination of it has been raised as a real actuality in modern church life. The rejection of the institutional character of the church has a long history. To understand the true nature and the true Scriptural functioning of a church order one needs to get perspective on the new order which was given by Christ by means of his Holy Spirit. The new order must be seen as the way of life that was created by Christ on the profound ground of the expiation. In this context a church order must be understood as existing in the movement from the believer to the Word which occurs in the leading of the Spirit through ordained means. Seen in this sense, a church order must be regarded as a modus quo by which the church is governed by Christ by means of his Spirit, in order to maintain the new order which He created for his children. Seen as such, a church order is not a man created dispensable burden for the church of Christ, furthermore it is not an anti-Spiritual instrument by which the church is plunged into a dreary existence of cold formalism. To the contrary, a true Scriptural church order must be appreciated as a valuable instrument through which the governing labour of Christ, by means of his Holy Spirit, in the church should become visible. A Scriptural church order is in essence a correction on the separation of the Holy Spirit from the Word of God. Therefore a Scriptural church order should be considered as indispensable in this world for church being, according to the new order of life in Christ.